Compatibility and coexistence between IMT-Advanced and fixed systems - Zaid Ahmed Shamsan, author; Lway Faisal AbdulRazak, 1982-, author; Tharek Abd. Rahman, author; International Conference on Information Technology and Multimedia (4th : 2008 : Kajang, Selangor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL